Meningkatkan Kemampuan Membaca Meningkatkan Kemampuan Membaca Menggunakan Metode Struktural Analitik Sintetik untuk Siswa Kelas 1 Sekolah Dasar - Riyasih Asih; Muhamad Sofian Hadi (Universitas Muhammadiyah Bangka Belitung, 2025)
This study aims to enhance the early reading and writing skills of first-grade students at SD Muhammadiyah Aimas through the Structural Analytic Synthetic (SAS) method. The motivation behind this research stems from the observation that students’ early reading skills were still below the Minimum Competency Criterion (KKM). This research is classified as Classroom Action Research (CAR), involving 20 students from grade 1 at SD Muhammadiyah Aimas as subjects. Data collection techniques included observation sheets, reading ability tests, and interviews. The results indicated that the learning implementation aspect improved from an average of 66% in Cycle I to 80% in Cycle II, categorizing it as